Molecular Classification of Vicia faba L Genotypes by Using RAPD-PCR Markers - Al-Talab, Noor; Al-mathidy, Aamer; Esho, Kamal (Edelweiss Applied Science and Technology, 2021)
The research included the molecular classification study of seven genotypes of the bean Vicia faba L. (FBSPN2, TLD1266, TLD1814, TLB1266, Luzdeotono, favad and Histal. Using the RAPD technique for DNA, as 13 random primers were used, the products of inflation were transferred within the agarose gel, and the results of the study showed the possibility of separating the genotypes from each other and determining the degree of genetic variation between them, as the primers used produced (1002) packages of them (417 normal bundles and (585) mixed bundles. The genetic differences of the studied genotypes were determined to be distinguished by the number of bundles, as they reached (28) bundles, including (13) unique bundles and (15) absent bundles. The ILB1266 genotype showed the highest number of unique bundles, which It reached 4 bundles, while the cultivar Favad showed the absence of unique bundles in it, either bundles are absent. The genotypes (ILD1266, IILB1266, Luzdeotono) were distinguished for having the highest number, which amounted to (3) bundles. As for the FBSPN2 genotype, it did not have any absent bundle, and the primers varied. Of the resulting bundle sizes, their sizes ranged between bp (1925-130), and the highest value for the genetic dimension ranged between (0.110 - 0.269), as the lowest genetic dimension was between the two structures (FBSPN2 and ILD1266), which amounted to 0.110, and the highest value for the genetic dimension was (0.2 69) between the genotypes (ILD1266, HISTAL) (ILD1266, Luzdeotono) The Dendrogram shows the separation of the studied genotypes into two main groups, and each of them into two subgroups.